Język w sprzedaży transakcyjnej i relacyjnej (na podstawie modelu SPIN) - Wal, Dawid (Słowo. Studia językoznawcze, 2017)
This text focuses on language comparation between transactional selling and relationship selling, including the SPIN model. Author gathers the real-life examples and analyzes the structure of the whole communication process in both selling strategies. Wal claims that SPIN model puts emphasis on the specific use of language: asking questions, uncovering needs and coaxing the wary customer, what is significant for building customer satisfaction and loyalty.